2016
DOI: 10.1186/s12872-016-0305-4
|View full text |Cite
|
Sign up to set email alerts
|

Arterial stiffness in patients with coronary artery disease: relation with in-stent restenosis following percutaneous coronary intervention

Abstract: BackgroundCoronary artery disease (CAD) is one of the most important issues in modern medicine due to its high mortality and prevalence. An early detection and prevention can reduce morbidity and mortality. Arterial stiffness is a potent and independent predictor of CAD. We aimed to investigate the arterial stiffness in CAD patients undergoing the coronary angiography. Also, we investigated a possible correlation between arterial stiffness and in-stent restenosis (ISR), an important limitation of percutaneous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 31 publications
1
18
0
2
Order By: Relevance
“…With regard to CAD, aortic stiffness is associated with a broad range of patients, from apparently healthy subjects to those with cardiovascular risks and stable CAD, to postcoronary intervention [25][26][27][28]. One clinical study demonstrated that increased aortic stiffness using brachial-ankle PWV measured by volume-plethysmography was an independent predictor of 3-year cardiovascular event-free survival in patients with established CAD [28].…”
Section: Relationship Between Aortic Stiffness and Myocardial Ischemiamentioning
confidence: 99%
“…With regard to CAD, aortic stiffness is associated with a broad range of patients, from apparently healthy subjects to those with cardiovascular risks and stable CAD, to postcoronary intervention [25][26][27][28]. One clinical study demonstrated that increased aortic stiffness using brachial-ankle PWV measured by volume-plethysmography was an independent predictor of 3-year cardiovascular event-free survival in patients with established CAD [28].…”
Section: Relationship Between Aortic Stiffness and Myocardial Ischemiamentioning
confidence: 99%
“…HIV is capable of penetrating endothelial cells and is able to initiate inflammatory and biochemical intracellular reactions in the coronary arteries [10], the cerebral vasculature [11], and the aortic wall [12]. Moreover, aortic stiffness is associated with coronary artery disease [13,14]; and it is an independent predictor of coronary events [15]. However, there are contradictory findings on aortic stiffness measured by carotid-femoral pulse wave velocity (cfPWV) in treatment-naïve individuals living with HIV; with some studies showing similar [16,17] and others increased cfPWV, compared to controls [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…HIV is capable to penetrate and to initiate inflammatory and biochemical intracellular reactions in the endothelial cells of the coronary arteries [9], the cerebral vasculature [10], and the aortic wall [11]. Moreover, aortic stiffness is associated with coronary artery disease [12,13] and is an independent predictor of coronary events [14], but there are contradictory findings on aortic stiffness measured by carotid-femoral pulse wave velocity (cfPWV) in the setting of recent HIV diagnosis without ART.…”
Section: Introductionmentioning
confidence: 99%